Water-based binder system for powder injection moulding process - Chin, Yiu Kang (2018)
Powder injection moulding has been an effective way of forming metal or ceramic parts with complex geometries such as turbochargers for automobiles and parts for planes. During the process, the metal or ceramic powder will be mixed with a polymer mixture known as binder, which will be removed in the final product. This process of binder removal, known as debinding, is traditionally done by submerging the moulded parts in a pool of chemical solvent such as acetone. However, usage of chemical solvent has risen concerns of environmental issues. Therefore, a binder system that can be processed by environmental friendly methods are desirable. In this project, a PEG based binder system that uses water soluble PEG as the primary binder will be reaseached on. Unlike the traditional kind of binder systems that requires chemical solvent to debind, this PEG primary binder can be removed using water instead of conventional chemical solvent during the debinding process, making it a lot environment friendly than previous solvent choices. Various polymers will be mixed with PEG to form the binder system, which then will be mixed together with metal powder and moulded with a powder injection moulding machine. Subsequently, the moulded green part will be debinded and sintered. Mechanical property tests such as tensile test and four-point bending test will be done to determine the feasibility of the binder system.